Pemikiran Ibn Taymīyah tentang Sharī‘ah sebagai Tujuan Tasawuf - Washil, Izzuddin; Fata, Ahmad Khoirul (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
Ibn Taym?yah rejects no all doctrines of Sufism although he criticizes some of them. He, for an instance, does firmly refuse altogether the doctrine of wa?dat al-wuj?d and fan??. Ibn Taym?yah has a unique concept of sufism, which differs from other concepts of Sufism promulgated by other sufis, especially those of Wuj?d?yah proponents. Ibn Taym?yah?s concept of Sufism puts great emphasis on it appropriateness with stipulations of shar??ah. The compatibility of shar??ah and tasawuf has been the main feature of his model of Sufism. When other Sufis start their mystical journey from the stage of shar??ah, Ibn Taym?yah puts shar??ah as the final stages. To him shar??ah is the main goal of mystical journeys; tasawuf should be based on shar??ah and it also must end to shar??ah. Using al-Taftaz?n??s perspective this study finds that the character of Ibn Taym?yah?s Sufism is Ta?awwuf Akhl?q?. This is so because he prefers to purify morality than such mystical experiences as wa?dat al-wuj?d or fan?? and the uses of symbols to reveal the mystical experiences.